Kryminalna topografia prowincji. Łagów Lubuski w "Cichej przystani" Marty Mizuro = Crime topography of the provinces. Łagów Lubuski in "Cicha Przystań" ("Silent Harbor") by Marta Mizuro - Gieba, Kamila (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an interpretation of the crime novel "Cicha Przystań" ("Silent Harbor") by Marta Mizuro. The intrigue is located in the provinces. The scene of crime is Łagow Lubuski, a small tourist town in the Lubuskie Lake District. The interpretation concerns three aspects associated with provincial space: literary topography and toponymy, symbols of cemetery and the ghosts of the place.
Keywords: Mizuro, Marta (1970- ); Łagów Lubuski; powieść kryminalna; literatura polska - 21 w.